Generation of amorphous carbon and crystallographic texture during low-temperature subseismic slip in calcite fault gouge - Piane, C.; Piazolo, S.; Timms, Nicholas Eric; Luzin, V.; Saunders, M.; Bourdet, J.; Giwelli, A.; Ben Clennell, M.; Kong, C.; Rickard, William; Verrall, M. (Geological Society of America, 2018)
Identification of the nano-scale to micro-scale mechanochemical processes occurring during fault slip is of fundamental importance to understand earthquake nucleation and propagation. Here we explore the micromechanical processes occurring during fault nucleation and slip at subseismic rates (∼3 × 10−6 m s–1) in carbonate rocks. We experimentally sheared calcite-rich travertine blocks at simulated upper crustal conditions, producing a nano-grained fault gouge. Strain in the gouge is accommodated by cataclastic comminution of calcite grains and concurrent crystal-plastic deformation through twinning and dislocation glide, producing a crystallographic preferred orientation (CPO). Continued wear of fine-grained gouge particles results in the mechanical decomposition of calcite and production of amorphous carbon. We show that CPO and the production of amorphous carbon, previously attributed to frictional heating and weakening during seismic slip, can be produced at low temperature during stable slip at subseismic rates without slip weakening.